Enchondromas - Bektaş, Mert; Gem, Kadir; Yalçın, Mehmet; Tosyalı, Hakan Koray (The European Research Journal, 2025)
Objectives: Enchondromas are benign cartilage tissue tumors composed of mature hyaline cartilage. Most enchondromas are discovered incidentally during radiological examinations. Differentiating between low-grade chondrosarcoma and enchondroma can be difficult both clinically, radiologically, and histologically. Malignant tumors can mimic benign tumors. Therefore, it is crucial to accurately diagnose enchondromas, as the treatments for both tumors are very different. We aimed to contribute to a better understanding of the clinical features and treatment challenges of patients diagnosed with enchondroma. Methods: Thirty patients who presented to the Department of Orthopedics and Traumatology at Manisa Celal Bayar University Faculty of Medicine between 2010 and 2023 and were diagnosed with enchondroma in hand after surgical treatment were retrospectively evaluated in our study. The patients were classified according to the Tordai and Takigawa classifications. Results: Nineteen women and 11 men were examined. The lesions were observed in the left hand in 15 patients and in the right hand in 15 patients. The proximal phalanx was the most affected area. Fractures developed in 2 patients during postoperatively, requiring revision surgeries. No wound complications were observed during follow-up, and except for 2 patients who experienced refractures, both clinical and radiological complete healing was observed at the 8-week follow-up. Conclusions: This study aims to understand better the clinical features and treatment challenges of patients diagnosed with enchondroma. We believe that immobilization for at least 4 weeks or implant application would be appropriate to increase stability in patients with intramedullary involvement of more than 50% in the dominant hand. Enchondromas still present many unknowns, more research is necessary to increase knowledge about these tumors. This study provides important data regarding enchondromas and serves as a foundational step for further research and investigation in this area.